Application of Bacillus subtilis for the Alleviation of Salinity Stress in Different Cultivars of Wheat (Tritium aestivum L.) - Saboor Gul; Sadia Javed; Muhammad Azeem; Amreen Aftab; Nazima Anwaar; Tahir Mehmood; Basit Zeshan (MDPI, 2023)
Salinity has a negative impact on the agricultural production of crops. It adversely affects the physiochemical properties of the soil and ecological balance of the area. Plant growth-promoting bacteria play a key role in the biological control of phyto-pathogens and abiotic stress including salinity. Four varieties of wheat crop (V1: Akbar 2019, V2: Dilkash 2021, V3: Faisalabad 2008, and V4: Subhani 2020) were compared for their salinity stress tolerance and response towards Bacillus subtilis NA2. A completely randomized design (4 wheat varieties × 3 salt stress levels × 3 replicate × 2 control and bacterial treatments = 72 pots) was adopted using distilled water as a control. Stress negatively affected the plant growth. However, plants primed with Bacillus subtilis NA2 showed improved growth (plant lengths 29.45% and increased biomass 33.23%). Overall, bacterial strain enhanced the levels of carotenoids (45.53%), anthocyanin (32.51%), ascorbic acid (41.53%), total soluble proteins (59.21%), chlorophyll contents (49.65%), and peroxidase activity (31.76%). Levels of malondialdehyde (27.42%) and hydrogen peroxide (20.37%), catalase (16.48%), and ascorbate peroxidase (19.24%) decreased. With commensurable benefits, it can be inferred from the above study that the Bacillus subtilis NA2 strain is beneficial for the better yield of wheat under salinity stress by improving the plant defense mechanism and may be adopted in future by farmers.